Disease management for improved millet production - Das, I K; Palanna, K B; Rajesh, G (Indian Farming, 2023)
Millets are a group of cereal grains used for human and animal consumption. Many diseases come in the way of high productivity of millets. There are more than a dozen major diseases that considerably affect cultivation of various millets like sorghum, pearl millet, and small millets (finger, foxtail, kodo, proso, little, barnyard and browntop millets). Millets being grown under low input agricultural conditions, management of disease by chemical is not recommended and mostly preventive measures are followed. The article describes major diseases of millets and various cost effective and economic ways of their management for higher productivity.